Spud - Clairmont, Patsy; Oeltjenbruns, Joni (Nashville, Tenn. : Tommy Nelson, 2006)
Meatball, Soccer, and Stinky MacKenzie, mice who live in the pantry, band together to fight off Spud, a rat with a reputation as a bully.
Keywords: Bullies -- Fiction; Brothers and sisters -- Fiction; Mice -- Fiction; Rats -- Fiction